1986
DOI: 10.1039/c39860001232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and heterodimetallic complexes of lateral macrobicyclic cryptands

Abstract: The macrobicyclic molecules (la-c) have been synthesized; they are heteroditopic ligands combining a 'soft' and a 'hard' binding subunit, which form lateral dinuclear cryptates such as [Rh+-CO, Mn+ C (la-c)] by selective complexation to a given site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 0 publications
0
28
1
Order By: Relevance
“…Protonation of these nitrogen atoms has been observed in the solid-state structure of (H 2 L 5 )(ClO 4 ) 2 . [40] The protonation constants determined for L 2 and L 8 are lower than those reported for the parent crown ether 4,13-diaza- [18]crown-6 (log K 1 = 9.40 and log K 2 = 7.47 in 95 % methanol, I = 0.1  Et 4 NClO 4 , 25°C). [41] This is in accordance with previous observations in which a diminution of the amine basicity has been observed upon N-alkylation of oxa-aza crown ligands.…”
Section: Thecontrasting
confidence: 50%
See 1 more Smart Citation
“…Protonation of these nitrogen atoms has been observed in the solid-state structure of (H 2 L 5 )(ClO 4 ) 2 . [40] The protonation constants determined for L 2 and L 8 are lower than those reported for the parent crown ether 4,13-diaza- [18]crown-6 (log K 1 = 9.40 and log K 2 = 7.47 in 95 % methanol, I = 0.1  Et 4 NClO 4 , 25°C). [41] This is in accordance with previous observations in which a diminution of the amine basicity has been observed upon N-alkylation of oxa-aza crown ligands.…”
Section: Thecontrasting
confidence: 50%
“…Moreover, they contain convergent binding groups that can be especially designed to match the functionality of the guest molecule. It has been shown that lateral macrobicycles behave as very versatile receptors that can be used as platforms to obtain mono- [13][14][15][16] and bimetallic [17] complexes with many different aims (i.e., to induce processes of "push-pull" dimetallic substrate activation) [18] and as receptors for organic molecules, [19] anions, [20] or contact-ion pairs. [21,22] We are interested in the relation between structure and stability of lead(II) complexes with macrocyclic ligands derived from crown ether platforms, as well as in the role of the lone-pair activity of Pb II in these kind of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they offer the advantage of being preorganised and therefore capable of profiting from the thermodynamic macrobicyclic effect. It has been shown that lateral macrobicycles behave as very versatile receptors that can be used as platforms to obtain homo-and heterometallic dinuclear complexes with many different aims, that is, to induce processes of "push-pull" dimetallic substrate activation [22] and as receptors for organic molecules [23] or contact ion pairs. [24,25] However, to date the recognition of anions by this type of receptor has remained much less explored than cation recognition.…”
Section: Introductionmentioning
confidence: 99%
“…The electrophilic character of the uranyl system has been well documented, especially its ability to coordinate organic carbonyl groups, such as that of urea, in its planar fifth coordination site,19 or to act as an electrophilic catalyst for Michael additions13a and acyl‐transfer reactions 20. Detection of an intramolecular interaction of the (NS 2 )Rh–CO group with crown‐ether‐complexed alkaline metal ions has been attempted 15b…”
Section: Introductionmentioning
confidence: 99%